2006
DOI: 10.1897/05-335r.1
|View full text |Cite
|
Sign up to set email alerts
|

From organisms to populations: Modeling aquatic toxicity data across two levels of biological organization

Abstract: A critical step in estimating the ecological effects of a toxicant is extrapolating organism-level response data across higher levels of biological organization. In the present study, the organism-to-population link is made for the mysid, Americamysis bahia, exposed to a range of concentrations of six toxicants. Organism-level responses observed were categorized as no effect, delayed reproduction, reduced overall reproduction, or both reduced overall reproduction and survival. Population multiplication rates o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 40 publications
2
13
0
Order By: Relevance
“…This strongly differed from decomposition analysis results. Similar differences were reported by other authors (Salice and Miller 2003; Raimondo and McKenney 2006). However, these two methods addressed different questions about the sensitivity of organisms to toxicants.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This strongly differed from decomposition analysis results. Similar differences were reported by other authors (Salice and Miller 2003; Raimondo and McKenney 2006). However, these two methods addressed different questions about the sensitivity of organisms to toxicants.…”
Section: Discussionsupporting
confidence: 92%
“…Salice and Miller (2003) stated that “decomposition analysis indicated that the vital rates that were altered when populations were exposed to Cd were not well predicted by elasticities”. Raimondo and McKenney (2006) concluded that “although elasticity analysis identifies the life stages that may be key targets for conservation efforts… the magnitude of change in population parameters is an equally important factor to consider during population-level risk assessment of toxicant exposure”. Hansen et al .…”
Section: Discussionmentioning
confidence: 99%
“…Kuhn et al (2000) found high correlations of 96h-LC50 values and toxicant concentrations where populations would begin to decline. These results have also been observed in later mysid population studies by Raimondo and McKenney (2006). Kuhn et al (2001) confirmed that mysid models generated from laboratoryderived survival and reproduction could predict population projections of mysids in laboratory conditions.…”
Section: Population Dynamicssupporting
confidence: 77%
“…In this analysis, reduced reproduction was the primary contributor to reduced population growth rate for most concentrations, emphasizing the importance of altered reproduction in mysid population-level risk assessment (Raimondo and McKenney, 2006). Previous population modeling efforts by Kuhn et al (2000Kuhn et al ( , 2001 were aimed at evaluating the ecological relevance of mysid bioassays and population models.…”
Section: Population Dynamicsmentioning
confidence: 97%
“…In other words, a compound cannot be assumed to cause the same degree of effect on the population growth rate as it does on survival or reproduction. This phenomenon is true for a variety of exposure scenarios with A. bahia (Raimondo and McKenney 2006;Grear 2016). Similarly, reproduction by adult nematodes is more sensitive to cadmium than juvenile period (duration as juvenile); however, change in juvenile period has a greater effect on population fitness than does adult reproduction (Kammenga et al 1996).…”
Section: Discussionmentioning
confidence: 81%